On the Sequencing of Reforms in Eastern Europe - Genberg, Hans. (Washington, D.C. : International Monetary Fund, 1991)
This paper discusses issues related to the sequencing of the reforms that are necessary to transform the economies in Eastern Europe into market economies. It is first argued that the transition path of these economies will be smoother and less costly if a clear statement of the ultimate goals of the reforms is made at the outset. Interdependence between different aspects of the reforms implies that an appropriate strategy is to move on a broad front from the very beginning of the transformation process dealing simultaneously with macroeconomic stabilization, price reforms and convertibility, and privatization of state enterprises. It is also argued that a rapid reform process is preferable to a gradual one.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet